J‐Aggregate‐Based FRET Monitoring of Drug Release from Polymer Nanoparticles with High Drug Loading. Issue 45 (15th September 2020) - Liu, Yun; Yang, Guangze; Jin, Song; Zhang, Run; Chen, Peng; Tengjisi,; Wang, Lianzhou; Chen, Dong; Weitz, David A.; Zhao, Chun‐Xia
Abstract: Understanding drug‐release kinetics is critical for the development of drug‐loaded nanoparticles. We developed a J‐aggregate‐based Förster‐resonance energy‐transfer (FRET) method to investigate the release of novel high‐drug‐loading (50 wt %) nanoparticles in comparison with low‐drug‐loading (0.5 wt %) nanoparticles. Single‐dye‐loaded nanoparticles form J‐aggregates because of the high dye‐loading (50 wt %), resulting in a large red‐shift (≈110 nm) in the fluorescence spectrum. Dual‐dye‐loaded nanoparticles with high dye‐loading using FRET pairs exhibited not only FRET but also a J‐aggregate red‐shift (116 nm). Using this J‐aggregate‐based FRET method, dye‐core–polymer‐shell nanoparticles showed two release processes intracellularly: the dissolution of the dye aggregates into dye molecules and the release of the dye molecules from the polymer shell. Also, the high‐dye‐loading nanoparticles (50 wt %) exhibited a slow release kinetics in serum and relatively quick release in cells, demonstrating their great potential in drug delivery. Abstract : A J‐aggregate‐based Förster‐resonance energy‐transfer (FRET) method to investigate the release of high‐drug‐loading (50 wt %) and low‐drug‐loading (0.5 wt %) nanoparticles is reported. The high‐dye‐loading nanoparticles exhibited a slow release kinetics in serum and a relatively quick release in cells, demonstrating their great potential in drug delivery.